2017
DOI: 10.1159/000480650
|View full text |Cite
|
Sign up to set email alerts
|

FSHR and LHR Expression and Signaling as Well as Maturation and Apoptosis of Cumulus-Oocyte Complexes Following Treatment with FSH Receptor Binding Inhibitor in Sheep

Abstract: Background/Aims: Currently, it remains unknown whether FSH receptor binding inhibitor (FRBI) influences follicular development and reproduction functions in humans and animals. The present study aimed to investigate FRBI effects on in vitro maturation (IVM) and apoptosis of cumulus-oocyte complexes (COCs) of sheep, to determine the effect of FRBI on mRNA and protein levels of FSHR and LHR in COCs, and to elucidate the signal pathway of FRBI effects. Methods: COCs were in vitro cultured for 24h in the IVM media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…On the other hand, the maturation rate was greatly decreased in FSH + LH treatment group. These observed results are different from those established in a previous report on IVM of oocytes in the presence of FSH + LH hormones (Manabe et al, 2004 (Song et al, 2014;Wei et al, 2017). Thus, autophagy is preferred over apoptosis during the oocyte maturation in the presence of rapamycin.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the maturation rate was greatly decreased in FSH + LH treatment group. These observed results are different from those established in a previous report on IVM of oocytes in the presence of FSH + LH hormones (Manabe et al, 2004 (Song et al, 2014;Wei et al, 2017). Thus, autophagy is preferred over apoptosis during the oocyte maturation in the presence of rapamycin.…”
Section: Discussioncontrasting
confidence: 99%
“…Our initial study revealed that the addition of 10 to 40 μg/mL FRBI into in vitro maturation (IVM) medium reduced the maturation rate, enhanced the apoptosis rate, and decreased the proliferation capacity of sheep cumulus-oocyte complex. Additionally, FRBI decreased FHS concentrations and increased estradiol (E 2 ) concentrations in the IVM medium (15). Currently, there is scarce information about effects of FRBI on the gene levels associated with ovarian cancers in humans and animals (16).…”
Section: Introductionmentioning
confidence: 99%
“…No nuclear atypia was found. Our results revealed supplement of FRBI into the IVM media could reduce the maturation rate, enhance the apoptosis rate, and decreased proliferation capacity of sheep COCs [ 11 ]. FRBI could suppress the mRNA and protein expression levels of FSHR and LHR in sheep cumulus-oocyte complex (COCs), additionally decreased FHS production and increased estradiol (E2) production of sheep COCs [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed supplement of FRBI into the IVM media could reduce the maturation rate, enhance the apoptosis rate, and decreased proliferation capacity of sheep COCs [ 11 ]. FRBI could suppress the mRNA and protein expression levels of FSHR and LHR in sheep cumulus-oocyte complex (COCs), additionally decreased FHS production and increased estradiol (E2) production of sheep COCs [ 11 , 12 ]. Up to date, no reports have as yet documented about FRBI effects on the ovarian oncogenesis and genes related to ovarian cancerin humans and animals [ 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%